Insights into the Control of Drug Release from Complex Immediate Release Formulations - Runqiao Dong; James C. DiNunzio; Brian P. Regler; Walter Wasylaschuk; Adam Socia; J. Axel Zeitler (MDPI AG, 2021)
The kinetics of water transport into tablets, and how it can be controlled by the formulation as well as the tablet microstructure, are of central importance in order to design and control the dissolution and drug release process, especially for immediate release tablets. This research employed terahertz pulsed imaging to measure the process of water penetrating through tablets using a flow cell. Tablets were prepared over a range of porosity between 10% to 20%. The formulations consist of two drugs (MK-8408: ruzasvir as a spray dried intermediate, and MK-3682: uprifosbuvir as a crystalline drug substance) and NaCl (0% to 20%) at varying levels of concentrations as well as other excipients. A power-law model is found to fit the liquid penetration exceptionally well (average <semantics>R2>0.995</semantics>). For each formulation, the rate of water penetration, extent of swelling and the USP dissolution rate were compared. A factorial analysis then revealed that the tablet porosity was the dominating factor for both liquid penetration and dissolution. NaCl more significantly influenced liquid penetration due to osmotic driving force as well as gelling suppression, but there appears to be little difference when NaCl loading in the formulation increases from 5% to 10%. The level of spray dried intermediate was observed to further limit the release of API in dissolution.